Legal environmental regulation and green technology innovation of energy enterprises: based on panel threshold regression - Xu, Didong; Chen, Yadi; Wang, Jia; Huang, Xiaoyue (Frontiers in Energy Research, 2023)
Legal environmental regulation is not only an important tool for green technology innovation and energy efficiency improvement, but also a key measure for enterprise upgrading and high-quality economic development. Based on the panel data of China’s listed energy companies from 2010 to 2020, this paper finds that legal environmental regulation has a significant positive impact on enterprise green technological innovation by using SYS-GMM. And the threshold regression model is used to examine the nonlinear impact of legal environmental regulation on green technology innovation in this paper. The results show that the positive impact of legal environmental regulation on green output of energy enterprises is more prominent than that of non-R&D investment. In addition, the impact of legal environmental regulation on green technology innovation of energy enterprises has a threshold effect. That is, the loose legal environmental regulation (LER ≤ 399.656) has a negative impact on the green output of energy enterprises, while the impact of strict legal environmental regulation (LER > 399.656) is the opposite. Meanwhile, the loose legal environmental regulation (LER ≤ 491.291) and strict legal environmental regulation (LER > 491.291) have a negative impact on the non-R&D investment of energy enterprises. Finally, there are huge differences in green technology innovation capabilities of energy enterprises.